PS-P14-2: ARTERIAL HYPERTENSION AND SALT CONSUMPTION IN LITHUANIA. (January 2023) - Zakauskiene, Urte; Sukackiene, Diana; Macioniene, Ernesta; Bratcikoviene, Nomeda; Banys, Valdas; Zabuliene, Lina; Miglinas, Marius
Abstract : Objective: Though it is an easily modifiable factor, high salt consumption remains the major contributor of the development of arterial hypertension and cardiovascular mortality. The World Health Organization recommends to consume less than 5 g salt per day. We aimed to evaluate the associations of 24-hour urinary sodium excretion and arterial blood pressure in Lithuanian adult population. Design and method: 1082 randomly selected individuals (18–69 years) were invited to participate in the study. We obtained 1035 samples of 24-hour urine collections, but 147 participants were excluded due to incomplete or inaccurate urine collection and/or 24 h urinary creatinine excretion outside 2 standard deviations of the sex-specific distribution. Three blood pressure (BP) readings were measured, separated by at least 1 min. Arterial hypertension was defined as systolic or diastolic BP > 140/90 mmHg and/or antihypertensive treatment and/or previously diagnosed hypertension. 9 individuals were excluded due to missing blood pressure measurements. Results: In a final analysis 879 individuals were enrolled, 52.67% was female. Mean age of all participants was 47.49 (±12.05) years old. Mean 24-hour urinary sodium excretion was 162.5mmol/24 hours and calculated mean salt consumption was 9.97 g (±5.29). Males had higher mean salt consumption than females (11.76 ± 5.8 g vs. 8.36 ± 4.2, p < 0.001). 35.7% of participants were identified to have arterial hypertension, a quarter were treated with antihypertensive medication. Hypertensive individuals had significantly higher salt consumption than normotensive participants of this study (11.1 ± 6.3 g vs. 9.35 ± 4.5 g, p < 0.01). Correlation coefficient between arterial hypertension and salt consumption was 0.25 (p < 0.001). Conclusions: Mean salt consumption in Lithuania twofold exceeds recommended amount. Male individuals use more salt than female. Hypertensive individuals have higher salt consumption.